Description of a new Chinese species of the genus Rhigognostis Staudinger, 1857 (Lepidoptera: Plutellidae) - E. Baraniak; K. Larsen (SHILAP)
Rhigognostis barkamensis Baraniak & Larsen, sp. n. is described from the northern part of Sichuan province in China on the basis of a single female specimen caught by light at Zhe Gu Shan pass near Barkam. The new species is compared with all known species of Rhigognostis Staudinger, 1857 and a differential diagnose is given.